Ageing dependence and martensite stabilization in copper based shape memory alloys - Adiguzel, O. (Iop Publishing Ltd, 2014)
Shape memory alloys exhibit a peculiar property called shape memory effect based on a first order solid state phase transformation, martensitic transformation which occurs in thermal manner on cooling the materials. Martensitic transformation is evaluated by the structural changes in microscopic scale. Copper-based ternary alloys exhibit shape memory effect in metastable beta phase region. These alloys have bcc-based ordered structures at high temperature, and transform martensiticaly to the long-period layered structures on cooling. The material atoms move cooperatively on {110}-type close packed planes of parent phase by means of a shear-like mechanism, and structural and fundamental properties of these alloys are altered by aging in the martensitic state. Therefore, the ageing gives rise to the structural changes in both long and short-range order in material. X-ray powder diffraction studies carried out in a long time interval on copper based shape memory alloys reveal that peak locations and intensities chance with ageing duration in martensitic condition, and these changes lead to the martensite stabilization in the redistribution or disordering manner, and stabilization proceeds by a diffusion-controlled process.
13th International Symposium on Advanced Materials (ISAM) -- SEP 23-27, 2013 -- Islamabad, PAKISTAN